2020
DOI: 10.1097/jcma.0000000000000221
|View full text |Cite
|
Sign up to set email alerts
|

Family physician system in Taiwan

Abstract: Following economic development and increasing healthcare demand, Taiwan has not only built a universal healthcare coverage payment system in 1995, but has also developed an accountable family physician system, called the Family Practice Integrated Care Project (FPICP), to deal with the pressures of an ageing society, since 2003. The community healthcare group-based family physician system is not only an important milestone for the development of family medicine in Taiwan but may also even serve as a global exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…Taiwan is a country with 23 million people, located at the eastern part of Asia. The Taiwan Medical Association was established in 1930, and there were over 49 thousand members in 2018, practicing in 22 medical specialties [ 14 ]. Family medicine, which topped the list of the specialties announced by the Ministry of Health and Welfare, was introduced to provide holistic care and to act as a gatekeeper of the health care system [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Taiwan is a country with 23 million people, located at the eastern part of Asia. The Taiwan Medical Association was established in 1930, and there were over 49 thousand members in 2018, practicing in 22 medical specialties [ 14 ]. Family medicine, which topped the list of the specialties announced by the Ministry of Health and Welfare, was introduced to provide holistic care and to act as a gatekeeper of the health care system [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…The database of the FPICP, with the help of these extra datasets, enables research specific to the family physician system in Taiwan and was first used in a recent publication by the authors. 3…”
Section: Settingmentioning
confidence: 99%
“…One major intervention is the establishment of the Family Practice Integrated Care Project (FPICP). 3 In brief, the FPICP is a modified pay-forperformance (P4P) programme that affects…”
Section: Introductionmentioning
confidence: 99%
“…A brief explanation of propensity-score matching in this study is shown in Appendix 2. According to our previous study, FPICP patients had slightly lower prevalence of several chronic diseases, including diabetes, hyperlipidaemia, heart failure, hypertension, coronary artery disease, peripheral vascular disease, systemic embolism, cerebral vascular disease, and chronic kidney disease [3]. The presence of these chronic conditions are related to diabetes or its complications (macrovascular or microvascular) [7], and would influence the physicians' behavior of ordering related examinations.…”
Section: Target Populationmentioning
confidence: 99%
“…The SARS outbreak reflected the insufficiency of endemic disease preventive function in Taiwan's communities. FPICP was launched to empower primary care physicians by providing additional resources and facilitating vertical integration between primary care clinics and community hospitals to build up a primary community care network [3].…”
Section: Introductionmentioning
confidence: 99%